Adult Migrants’ Language Learning, Labour Market, and Social Inclusion - Fejes, Andreas (2023)
In this thematic issue, we present up‐to‐date research from authors who problematise the various links between adult migrants’ language learning, education, the labour market, and social inclusion. Some contributions are more focused on the relation between education and social inclusion, while others emphasise links between language learning, the labour market, and social inclusion. Together, authors in this thematic issue point to the multiple challenges migrants face when trying to establish themselves in a new country.